Earning response coefficients and the financial risks of China commercial banks - Cheng, Fan Fah; Md Nassir, Annuar (World Business Institute, 2010)
This paper reports new findings of a significant relationship between financial risks, price risk, market risk, foreign exchange and earnings response coefficients of commercial banks: The financial risks are interest rate risk, liquidity risk, credit risk and solvency risk. The methodology used is the well accepted earnings-to-share price relation regression with the risks as the controlling factors. Overall, the study discovers that China commercial banks have a very strong returns-to-earnings relation. Test results indicate that the liquidity risk factors of China commercial banks contributed significantly to the returns-to-earnings relation. The liquidity risk contains the information beyond earnings changes in the return-to-earnings relation. These findings suggest that lending and borrowing activities of banks will be considered as efficient if activities reduce the liquidity risk through the proper asset-liability management. The results are plausible as they show the importance of asset-liability management in commercial banks.